1978
DOI: 10.1042/bj1690589
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and partial characterization of rabbit plasma α1-antitrypsin

Abstract: Alpha1-Antitrypsin was isolated from rabbit plasma by salting out with (NH4)2SO4 followed by ion-exchange chromatography either on DEAE-Sephadex or DEAE-cellulose (each at pH8.8 and 6.5), and affinity chromatography on Sepharose-Cibacron Blue and Sepharose-concanavalin A. The protein thus obtained was homogeneous during crossed immunoelectrophoresis by using an antiserum to whole rabbit plasma, but it migrated as two broad bands when electrophoresed in alkaline polyacrylamide gels. Under optimal loading condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…7A), both control and 7-day BALF samples showed two ␣ 1 -AT immunoreactive bands in the range of 52-60 kDa, corresponding to the native ␣ 1 -AT described in rodents (23). As a result of elastase instillation, the two-band pattern for the native ␣ 1 -AT became more evident and, two new bands were observed.…”
Section: Species Differences In Balf ␣ 1 -At Electrophoretic Patternmentioning
confidence: 99%
“…7A), both control and 7-day BALF samples showed two ␣ 1 -AT immunoreactive bands in the range of 52-60 kDa, corresponding to the native ␣ 1 -AT described in rodents (23). As a result of elastase instillation, the two-band pattern for the native ␣ 1 -AT became more evident and, two new bands were observed.…”
Section: Species Differences In Balf ␣ 1 -At Electrophoretic Patternmentioning
confidence: 99%
“…The homologous protein has been purified from the monkey (Berninger and Mathis 1976), horse (Pellegrini and Fellenberg 1980), dog (Abrams et al 1978), rabbit (Koj et al 1978), and rat (Takahara et al 1980; Ikehara et al 1981).…”
mentioning
confidence: 99%
“…This is concluded from the observations that (i) mouse contrapsin, like RPI II, is inhibitory towards trypsin but does not affect the activity of chymotrypsin or elastase, (ii) in sodium dodecyl sulphate/polyacrylamide-gel electrophoresis mouse contrapsin migrates as a molecule with an Mr of 64000, a value almost identical with that found for RPI II (65000), and (iii) neither inhibitor immunologically cross-reacts with cxl-PI. A number of mammalian sera, such as those of man (Yoshida & Mega, 1979), rabbit (Koj et al, 1978), dog (Abrams et al, 1978), horse (Pellegrini & von Fellenberg, 1980), mouse (Takahara & Sinohara, 1982) and rat (Rosenberg et al, 1976), have been reported to contain two or more forms of a1-PI, which can be separated by polyacrylamidegel electrophoresis. Mouse and rat, however are unique among them, since their two isoforms do not cross-react immunologically, whereas those from the other species are immunologically identical.…”
Section: Discussionmentioning
confidence: 99%
“…a1-PI has been isolated and characterized not only from man (Pannell et al, 1974) but also from plasma of several mammals, such as rabbit (Koj et al, 1978), mouse (Takahara & Sinohara, 1982) and rat (Rosenberg et al, 1976;Ikehara et al, 1981;Roll & Glew, 1981;Thisner & Rosengren, 1982 serum (Dahlmann et al, 1981), we used, in the present study, a new preparative ion-exchange medium (Duppel, 1982), together with two conventional steps, to purify a1-PI to homogeneity. In addition, two similar, but functionally distinct, proteinase inhibitors, tentatively designated RPI I and RPI II, were purified.…”
mentioning
confidence: 99%